Copper-phosphorus / foam cobalt composite catalyst and preparation method and application thereof

By preparing copper-phosphorus/foam cobalt composite catalysts, the problem of insufficient catalyst activity and stability in the prior art is solved, and efficient and stable electrochemical synthesis of ammonia is achieved, reducing costs and resource consumption.

CN119877023AActive Publication Date: 2025-04-25SOUTHWEST PETROLEUM UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510364473.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

In the prior art, in the process of electrochemical ammonia synthesis, the activity and stability of the catalyst are insufficient, resulting in low ammonia yield, high cost of precious metal catalysts and scarce resources, and the activity and selectivity of non-precious metal catalysts such as pure cobalt materials in nitrate reduction synthesis ammonia reaction.

Method used

The copper-phosphorus/foam cobalt composite catalyst was used to obtain the foam cobalt for pretreatment, alkali treatment to form a cobalt hydroxyoxide precursor, copper plating electrodeposition and phosphating annealing treatment, and a catalyst with excellent electrochemical activity and stability was prepared.

Benefits of technology

It significantly improves the ammonia production efficiency of nitrate reduction synthesis, reduces the reaction dynamic potential energy, and has good stability and low cost, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877023A_ABST
    Figure CN119877023A_ABST
Patent Text Reader

Abstract

The invention discloses a copper-phosphorus / foam cobalt composite catalyst and a preparation method and application thereof, and belongs to the technical field of catalysts. The preparation method comprises the following steps that S1, foam cobalt is obtained, and the foam cobalt is pretreated; s2, carrying out alkali treatment on the pretreated foam cobalt to obtain a hydroxyl cobalt oxide precursor with a double-layer oxyhydrogen structure; s3, preparing a copper plating electrolyte, and placing the hydroxyl cobalt oxide precursor in the copper plating electrolyte for electro-deposition to obtain a copper / foam cobalt precursor; and S4, carrying out phosphating annealing treatment on the copper / foam cobalt precursor to obtain the copper-phosphorus / foam cobalt composite catalyst. The preparation method is simple and low in cost, and the prepared copper-phosphorus / foam cobalt composite catalyst has excellent activity and stability and can be suitable for a nitrate electrochemical reduction ammonia synthesis reaction, the reaction dynamic potential energy of nitrate reduction ammonia preparation is reduced, and the ammonia preparation efficiency is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a copper-phosphorus / foamed cobalt composite catalyst and a preparation method and application thereof. Background Art

[0002] As the global energy structure transforms toward clean and low-carbon energy, green synthetic ammonia technology, as an important chemical production process, has received widespread attention. Ammonia is not only a key raw material for fertilizer production, but is also seen as a potential clean energy carrier. The traditional Haber-Bosch process is currently the main method for industrial ammonia synthesis, but it relies on fossil fuels as a hydrogen source, has harsh reaction conditions (high temperature and high pressure), and is accompanied by a large amount of carbon dioxide emissions, which is not conducive to sustainable development. Therefore, the development of green and low-carbon synthetic ammonia technology has become a hot topic in current research.

[0003] Electrochemical synthesis of ammonia is a promising green ammonia production method. This technology uses electrochemical reactions to convert nitrogen or nitrate into ammonia. When nitrogen is used as a nitrogen source, the ammonia yield is extremely low (about 0.1~100 μg h) due to its poor solubility in water, strong N≡N bond energy, difficulty in activation, and the limitation of competitive hydrogen evolution reaction. -1 mg cat -1 ), so this technology still cannot be used for large-scale production of ammonia. When nitrate is used as a nitrogen source, it can not only realize the resource utilization of nitrate in wastewater, but also reduce dependence on fossil fuels and reduce carbon emissions. However, the core challenge of nitrate reduction electrochemical reaction lies in the development of efficient and stable catalysts.

[0004] At present, precious metal catalysts such as platinum, palladium, and ruthenium have high catalytic activity, but their high cost and scarce resources limit their large-scale application. In addition, the single-crystal copper metal element, which is a catalyst with excellent performance, will have stability problems due to the strong adsorption of intermediate nitrogen-containing substances, and is prone to rapid deactivation during the reduction process. Moreover, at low overpotentials, the weak adsorption of hydrogen radicals on Cu will limit the hydrogenation rate. At high overpotentials, the dominant hydrogen evolution reaction will result in insufficient conversion of ammonia products.

[0005] Cobalt-based materials are considered to be a potential candidate for non-precious metal catalysts due to their abundant natural resources, low cost and good performance. However, the activity and selectivity of pure cobalt materials in the nitrate reduction reaction to synthesize ammonia are insufficient, making it difficult to meet the needs of practical applications. Summary of the invention

[0006] In view of the above problems, the present invention aims to provide a copper-phosphorus / foamed cobalt composite catalyst and a preparation method and application thereof.

[0007] The technical solution of the present invention is as follows: On the one hand, a method for preparing a copper-phosphorus / foamed cobalt composite catalyst is provided, comprising the following steps: S1: obtaining foamed cobalt and pretreating the foamed cobalt; S2: treating the pretreated cobalt foam with alkali to obtain a cobalt oxyhydroxide precursor having a double-layer hydroxyl structure; S3: preparing a copper plating electrolyte, and placing the cobalt oxyhydroxide precursor in the copper plating electrolyte for electrodeposition to obtain a copper / foam cobalt precursor; S4: performing phosphating annealing treatment on the copper / foam cobalt precursor to obtain the copper-phosphorus / foam cobalt composite catalyst.

[0008] Preferably, in step S1, the pretreatment comprises ultrasonic cleaning using hydrochloric acid solution, anhydrous ethanol and deionized water in sequence.

[0009] Preferably, in step S2, when the alkali treatment is performed, the pretreated cobalt foam is placed in a sodium hydroxide solution and kept warm at 75-85° C. for 12-14 hours.

[0010] Preferably, the concentration of the sodium hydroxide solution is 1-4 mol / L.

[0011] Preferably, in step S3, the electrolyte of the copper plating electrolyte is any one or more of copper chloride, copper sulfate, and copper nitrate.

[0012] Preferably, the concentration of the copper plating electrolyte is 1-4 mol / L.

[0013] Preferably, in step S3, during the electrodeposition, the electrodeposition is performed at a constant voltage of -2 to -2.5 V vs. RHE for 100 to 600 s.

[0014] Preferably, in step S4, the phosphating annealing treatment of the copper / cobalt foam precursor specifically includes the following sub-steps: placing the copper / cobalt foam precursor and sodium hypophosphite powder in a tube furnace, heating to 400° C. at 1-3° C. / min in an argon atmosphere, and keeping the temperature for 20-30 min.

[0015] On the other hand, a copper-phosphorus / foam cobalt composite catalyst prepared by any of the above-mentioned preparation methods of the copper-phosphorus / foam cobalt composite catalyst is provided, and its application in nitrate reduction to synthesize ammonia is provided.

[0016] The beneficial effects of the present invention are: The preparation method of the invention is simple and low in cost. The prepared copper-phosphorus / foam cobalt composite catalyst has excellent electrochemical activity and stability, can be applied to the electrocatalytic nitrate reduction reaction for synthesizing ammonia, reduces the reaction kinetic potential energy of nitrate reduction to produce ammonia, and significantly improves the efficiency of producing ammonia. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0018] Figure 1 The figure is a schematic flow chart of the preparation method of the copper-phosphorus / foamed cobalt composite catalyst of the present invention; Figure 2 This is a surface SEM image of the copper-phosphorus / foam cobalt composite catalyst of Example 1; Figure 3 This is a TEM image of the copper-phosphorus / foam cobalt composite catalyst of Example 1; Figure 4 The XRD diagram of the copper-phosphorus / foam cobalt composite catalyst before and after the electrochemical ammonia synthesis reaction in Example 1; Figure 5 The ammonia production activity and Faraday efficiency diagram of the copper-phosphorus / foam cobalt composite catalyst of Example 1; Figure 6 This is a long-term electrolysis stability test of the copper-phosphorus / foam cobalt composite catalyst of Example 1 at -0.3 V vs. RHE; Figure 7 The product content of the copper-phosphorus / foamed cobalt composite catalyst in the nitric acid reduction process of Example 1 changes with time; Figure 8 This is a cyclability test of the copper-phosphorus / foam cobalt composite catalyst of Example 1 at -0.3 V vs. RHE. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.

[0020] On the one hand, if Figure 1 As shown, the present invention provides a method for preparing a copper-phosphorus / foamed cobalt composite catalyst, comprising the following steps: S1: obtaining foamed cobalt and pretreating the foamed cobalt.

[0021] In a specific embodiment, the pretreatment includes ultrasonic cleaning using hydrochloric acid solution, anhydrous ethanol and deionized water in sequence. Optionally, the concentration of the hydrochloric acid solution is 0.5-1 mol / L, and the ultrasonic cleaning time is 15-20 min.

[0022] It should be noted that the purpose of pretreatment is to remove impurities such as oxides and organic matter on the surface of the foamed cobalt. In addition to the preferred pretreatment method in the above embodiment, other pretreatment methods in the prior art that can achieve this purpose can also be applied to the present invention.

[0023] S2: treating the pretreated cobalt foam with alkali to obtain a cobalt oxyhydroxide precursor having a double-layer hydroxyl structure.

[0024] In a specific embodiment, during the alkali treatment, the pretreated cobalt foam is placed in a sodium hydroxide solution and kept warm at 75-85° C. for 12-14 hours. Optionally, the concentration of the sodium hydroxide solution is 1-4 mol / L.

[0025] It should be noted that the purpose of the alkali treatment is to hydroxylate the cobalt foam to form a hydroxyl cobalt oxide precursor having a double-layer hydroxyl structure. In addition to the alkali treatment method of the above embodiment, the alkali treatment method formed by changing the type of alkali (such as potassium hydroxide, etc.), the concentration of the alkali, the temperature and time of the alkali treatment, etc., as long as it can achieve this purpose, the corresponding alkali treatment method can also be applied to the present invention.

[0026] S3: preparing a copper plating electrolyte, and placing the cobalt oxyhydroxide precursor in the copper plating electrolyte for electrodeposition to obtain a copper / foam cobalt precursor.

[0027] In a specific embodiment, the electrolyte of the copper plating electrolyte is any one or more of copper chloride, copper sulfate, and copper nitrate. Optionally, the concentration of the copper plating electrolyte is 1-4 mol / L.

[0028] In a specific embodiment, during the electrodeposition, the electrodeposition is performed at a constant voltage of -2 to -2.5 V vs. RHE for 100 to 600 s.

[0029] It should be noted that electrodeposition copper plating is a prior art, and the copper plating electrolyte and electrodeposition parameters of the above-mentioned embodiments are only preferred embodiments of the present invention. Other copper plating electrolytes and electrodeposition parameters that can also achieve electrodeposition copper plating are also applicable to the present invention.

[0030] S4: performing phosphating annealing treatment on the copper / foam cobalt precursor to obtain the copper-phosphorus / foam cobalt composite catalyst.

[0031] In a specific embodiment, the phosphating annealing treatment of the copper / cobalt foam precursor specifically includes the following sub-steps: placing the copper / cobalt foam precursor and sodium hypophosphite powder in a tube furnace, heating to 400° C. at 1-3° C. / min in an argon atmosphere, and keeping the temperature for 20-30 minutes.

[0032] It should be noted that phosphating annealing treatment is a prior art, and the phosphating annealing parameters of the above embodiment are only preferred embodiment parameters of the present invention, and other parameters that can also achieve phosphating annealing treatment can also be applied to the present invention.

[0033] In the present invention, the preparation method of the copper-phosphorus / foamed cobalt composite catalyst uses foamed cobalt as a substrate, and then covers the foamed cobalt substrate with a coating layer composed of phosphorus nanoparticles and copper nanoparticles, thereby retaining the macroporous framework structure of the foamed cobalt substrate, and the phosphorus nanoparticles and the copper nanoparticles are evenly distributed on the surface of the foamed cobalt substrate, presenting a sheet structure of nanoparticle accumulation.

[0034] On the other hand, the present invention also provides a copper-phosphorus / foam cobalt composite catalyst prepared by any of the above-mentioned methods for preparing the copper-phosphorus / foam cobalt composite catalyst and its use in nitrate reduction to synthesize ammonia.

[0035] In a specific embodiment, when the copper-phosphorus / foam cobalt composite catalyst of the present invention is used to synthesize ammonia by nitrate reduction, the copper-phosphorus / foam cobalt composite catalyst is used as the cathode electrode, and the nitrate solution is used as the electrolyte to electrocatalytically reduce nitrate to produce ammonia in a three-electrode electrochemical system.

[0036] Optionally, the nitrate solution is any one or more of a sodium nitrate solution, a potassium nitrate solution, a sodium nitrite solution, and a potassium nitrite solution, the concentration of the nitrate solution is 0.1-2 mol / L, the solvent of the nitrate solution is a sodium hydroxide solution or a potassium hydroxide solution, the pH of the nitrate solution is 13-14, and the voltage of the electrocatalytic reduction of nitrate is 0-0.3 V relative to the standard hydrogen electrode potential. In this embodiment, by using an alkaline nitrate solution, the conductivity of the solution can be increased and the rate of the electrolysis reaction can be accelerated.

[0037] It should be noted that electrochemical synthesis of ammonia using a catalyst is a prior art, and the parameters for electrochemical synthesis of ammonia in the above-mentioned embodiment are only preferred parameters of the present invention. Other methods for electrochemical synthesis of ammonia using a catalyst with changed parameters may also be applicable to the present invention.

[0038] Example 1 A copper-phosphorus / foamed cobalt composite catalyst is prepared by the following steps: (1) obtaining a cobalt foam (size: 2.0 cm×2.0 cm×0.2 cm), and pre-treating the cobalt foam, specifically: ultrasonically cleaning the cobalt foam in a dilute hydrochloric acid solution (concentration: 1 mol / L) and ethanol for 15 min, respectively, to remove surface oil and oxides, and then ultrasonically cleaning the cobalt foam in deionized water for 15 min, rinsing and drying the cobalt foam for later use; (2) placing the pretreated cobalt foam in 70 mL of a sodium hydroxide solution (concentration of 4 mol / L) and keeping it in an oil bath at 80°C for 12 h. After the insulation, cooling, washing and drying are performed to obtain a cobalt oxyhydroxide precursor having a double-layer hydroxyl structure; (3) preparing a copper plating electrolyte (a copper chloride solution with a concentration of 4 mol / L) as an electrodeposition solution, using the cobalt oxyhydroxide precursor as a working electrode, and a platinum sheet as a counter electrode, using an electrochemical workstation, and electroplating for 300 s at a constant voltage of -2.0107 V vs. RHE to obtain a copper / cobalt foam precursor; (4) The copper / foamed cobalt precursor was placed in a tubular furnace, and 0.5 g and 0.1 g of sodium hypophosphite powder were placed upstream and downstream, respectively. The temperature was raised to 400° C. at 2° C. / min in an argon atmosphere and kept at this temperature for 30 min to obtain the copper-phosphorus / foamed cobalt composite catalyst.

[0039] Example 2 Different from Example 1, the electrodeposition time of step (3) in this example is 100s, 200s, 400s, 500s, and 600s, respectively.

[0040] Example 3 Different from Example 1, the phosphating annealing treatment time in step (4) of this example is 1 h, 1.5 h, and 2 h respectively.

[0041] Comparative Example 1 Different from Example 1, this comparative example does not include steps (2) to (4), that is, the pretreated cobalt foam is used as the pure cobalt catalyst.

[0042] Comparative Example 2 Different from Example 1, this comparative example does not include step (3), that is, directly subjecting the cobalt oxyhydroxide precursor to a phosphating annealing treatment to obtain a phosphorus / cobalt foam catalyst.

[0043] Comparative Example 3 Different from Example 1, this comparative example does not include step (4), that is, no phosphating annealing treatment is performed to obtain a copper / foam cobalt catalyst.

[0044] Comparative Example 4 Different from Example 1, the substrate in step (1) of this comparative example is foamed copper, and the cobalt plating electrolyte (cobalt chloride solution with a concentration of 4 mol / L) is prepared in step (3) to electro-deposit cobalt to obtain a cobalt-phosphorus / foamed copper catalyst.

[0045] Comparative Example 5 Different from Example 1, this comparative example does not include step (2), that is, no alkali treatment is performed to obtain a copper-phosphorus / foam cobalt catalyst that is not alkali treated.

[0046] Test Case The morphology of the catalysts in each example and each comparative example was observed using a Geminisem 300 scanning electron microscope (SEM, Zeiss, Germany) and a transmission electron microscope. The surface SEM image of the copper-phosphorus / foam cobalt composite catalyst in Example 1 is shown in FIG. Figure 2 As shown, the TEM image of the copper-phosphorus / foam cobalt composite catalyst of Example 1 is as follows Figure 3 As shown. Figure 2 and Figure 3 It can be seen that the surface of the copper-phosphorus / foam cobalt composite catalyst of the present invention presents an irregular stacking matrix morphology and has a polycrystalline property. This is because the copper-phosphorus / foam cobalt composite catalyst of the present invention is composed of many copper nanoparticles and phosphorus nanoparticles with different orientations.

[0047] The structures of the catalysts in each example and each comparative example were observed by X-ray diffractometer. The XRD pattern of the copper-phosphorus / foam cobalt composite catalyst in Example 1 is as follows: Figure 4 As shown, (a) is the XRD spectrum of the copper-phosphorus / foam cobalt composite catalyst of the present invention before the electrochemical synthesis of ammonia reaction, and (b) is the XRD spectrum of the copper-phosphorus / foam cobalt composite catalyst of the present invention after 200 hours of electrochemical synthesis of ammonia reaction. Figure 4 It can be seen that the main peak position does not shift before and after the reaction and the types of peaks do not decrease significantly. This shows that the structure of the copper-phosphorus / foam cobalt composite catalyst of the present invention does not collapse after continuous reaction, indicating that the copper-phosphorus / foam cobalt composite catalyst of the present invention has good material structure stability. Combined with SEM and TEM images, it is shown that the irregular stacking matrix can improve the stability of the catalyst material.

[0048] The catalysts of each embodiment and each comparative example were used to synthesize ammonia by nitrate reduction. Electrochemical measurements were performed on a three-electrode electrochemical workstation (CHI760E) in an electrolyte of 1 mol / L KOH+0.1 mol / L KNO3 at a voltage of -0.3 V vs. RHE. The Faraday efficiency and ammonia production rate were analyzed, and nitrate reduction was performed for a long time and multiple cycles at a potential of -0.3 V vs. RHE to verify the stability of the copper-phosphorus / foam cobalt composite catalyst. The copper-phosphorus / foam cobalt composite catalyst, platinum sheet and Hg / HgO of the present invention were used as the working electrode, counter electrode and reference electrode, respectively. The linear sweep voltammetry (LSV) test was performed at a scan rate of 10 mV s -1 The method for testing ammonia production is to take the reaction solution after constant potential nitric acid reduction for 30 minutes at different potentials, dilute the concentration by an appropriate multiple, test the absorbance using the salicylic acid colorimetric method, and calculate the ammonia production rate according to the fitting formula of the standard curve. The Faraday efficiency is calculated according to the formula FE = (number of moles of product × molar mass of product) / (number of input charges × electron charge). Some test results are shown in Table 1 and Figure 5-Figure 8 shown.

[0049] Table 1 Performance test results of various embodiments and comparative examples

[0050] from Figure 5 It can be seen that the Faraday efficiency of the copper-phosphorus / foam cobalt composite catalyst prepared in Example 1 ranges from 60% to about 80% from 0 V to -0.4 V vs. RHE, showing a trend of first increasing and then decreasing, reaching a maximum of 80.2% at -0.3 V vs. RHE. The ammonia production rate shows a trend of gradually increasing and stabilizing.

[0051] from Figure 6 It can be seen that the production of ammonium and nitrite and the consumption of nitrate of the copper-phosphorus / foam cobalt composite catalyst prepared in Example 1 at -0.3 V vs. RHE. Specifically: as time goes by, NO3 - -N content from 0.0135 min -1 Gradually increase to 0.0398 min -1 , which is due to the enhanced electron availability or the atomic hydrogen radical being at more negative potentials. As the potential continues to rise, the nitrate removal rate tends to stabilize, indicating that the increase in removal rate may not be able to offset the decrease in energy utilization caused by high voltage, and the excess hydrogen tends to recombine into hydrogen. In addition, the generation of hydrogen bubbles will hinder the reaction active sites and hinder the adsorption of nitrates and other intermediates. The copper-phosphorus / foam cobalt composite catalyst of the present invention can have high catalytic activity at low overpotential.

[0052] from Figure 7 It can be seen that the copper-phosphorus / foam cobalt composite catalyst prepared in Example 1 did not show a sharp change in current density during the long-term electrolysis process in the strong alkaline solution, indicating that the copper-phosphorus / foam cobalt composite catalyst of the present invention has good stability.

[0053] from Figure 8 It can be seen that during the 22 nitric acid reduction processes at a potential of -0.3 V vs. RHE for the copper-phosphorus / foam cobalt composite catalyst prepared in Example 1, the yield of ammonia produced by electrocatalytic nitric acid reduction and the Faraday efficiency during the entire cycle did not change significantly, indicating that the copper-phosphorus / foam cobalt composite catalyst of the present invention has good stability.

[0054] As can be seen from Table 1, the pure cobalt catalyst (Comparative Example 1) and the phosphorus / foam cobalt catalyst without copper electrodeposition plating (Comparative Example 2) cannot reach the ammonia production rate and Faraday efficiency that can be achieved by the present invention. Although the copper / foam cobalt catalyst without phosphating treatment (Comparative Example 3) can reach a Faraday efficiency of about 71%, its stability is poor. If the foam copper is used as the substrate, cobalt is plated thereon, and then the cobalt-phosphorus / foam copper catalyst obtained by phosphating annealing treatment (Comparative Example 4) and the copper-phosphorus / foam cobalt catalyst without alkali treatment (Comparative Example 5) obtained without alkali treatment, the ammonia production efficiency cannot reach the ammonia production efficiency that can be achieved by the present invention, and the Faraday efficiency cannot reach the Faraday efficiency that can be achieved by the present invention, and particle aggregation will occur during the stability test.

[0055] In summary, the present invention can produce a copper-phosphorus / foam cobalt catalyst with good catalytic activity, high stability and no aggregation. Compared with the prior art, the present invention has significant progress.

[0056] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical contents to make some changes or modifications to the embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a copper-phosphorus / foamed cobalt composite catalyst, characterized in that: The following steps are involved: S1: obtaining foamed cobalt and pretreating the foamed cobalt; S2: treating the pretreated cobalt foam with alkali to obtain a cobalt oxyhydroxide precursor having a double-layer hydroxyl structure; S3: preparing a copper plating electrolyte, and placing the cobalt oxyhydroxide precursor in the copper plating electrolyte for electrodeposition to obtain a copper / foam cobalt precursor; S4: performing phosphating annealing treatment on the copper / foam cobalt precursor to obtain the copper-phosphorus / foam cobalt composite catalyst.

2. The method for preparing the copper-phosphorus / foamed cobalt composite catalyst according to claim 1, characterized in that: In step S1, the pretreatment includes ultrasonic cleaning using hydrochloric acid solution, anhydrous ethanol and deionized water in sequence.

3. The method for preparing the copper-phosphorus / foamed cobalt composite catalyst according to claim 1, characterized in that: In step S2, when the alkali treatment is performed, the pretreated foamed cobalt is placed in a sodium hydroxide solution and kept warm at 75-85° C. for 12-14 hours.

4. The method for preparing the copper-phosphorus / foamed cobalt composite catalyst according to claim 3, characterized in that: The concentration of the sodium hydroxide solution is 1-4 mol / L.

5. The method for preparing the copper-phosphorus / foamed cobalt composite catalyst according to claim 1, characterized in that: In step S3, the electrolyte of the copper plating electrolyte is any one or more of copper chloride, copper sulfate, and copper nitrate.

6. The method for preparing the copper-phosphorus / foamed cobalt composite catalyst according to claim 5, characterized in that: The concentration of the copper plating electrolyte is 1-4 mol / L.

7. The method for preparing the copper-phosphorus / foamed cobalt composite catalyst according to claim 1, characterized in that: In step S3, when the electrodeposition is performed, the electrodeposition is performed at a constant voltage of -2 to -2.5 V vs. RHE for 100 to 600 s.

8. The method for preparing the copper-phosphorus / foamed cobalt composite catalyst according to claim 1, characterized in that: In step S4, the copper / cobalt foam precursor is subjected to phosphating annealing treatment, which specifically includes the following sub-steps: placing the copper / cobalt foam precursor and sodium hypophosphite powder in a tube furnace, heating to 400° C. at 1-3° C. / min in an argon atmosphere, and keeping the temperature for 20-30 min.

9. A copper-phosphorus / foam cobalt composite catalyst, characterized in that: The catalyst is prepared by the method for preparing the copper-phosphorus / foamed cobalt composite catalyst described in any one of claims 1 to 8.

10. Use of the copper-phosphorus / foamed cobalt composite catalyst as claimed in claim 9 in synthesizing ammonia by nitrate reduction.

Citation Information

Patent Citations

  • Phosphorus and oxygen co-doped copper-based catalyst as well as preparation method and application thereof

    CN113789541A

  • Electrocatalytic nitrate reduction ammonia production catalyst and preparation method and application thereof

    CN115233253A

  • Method for preparing ammonia by reducing nitrate by using bimetallic phosphide three-dimensional self-supporting electrocatalyst

    CN115537847A

  • Heteroatom doped metal / transition metal phosphide catalyst and preparation method thereof

    CN117265582A

  • Stable copper-based catalyst for preparing ammonia through electrochemical nitrate reduction as well as preparation method and application of stable copper-based catalyst

    CN117385401A